INTELLECTUAL CAPITAL DISCLOSURE OF COMMERCIAL BANKS IN INDONESIA: AUDIT COMMITTEE COMPETENCY AND THE MODERATING ROLE OF CORPORATE OWNERSHIP - Muhammad Abilio Fauzan; Bima Cinintya Pratama; Eko Hariyanto; Tiara Pandansari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to examine the effect of aspects of good corporate governance, namely audit committee competence and concentration of ownership and institutional ownership on Intellectual Capital Disclosure, and consider the moderating effect of concentration of ownership and institutional ownership on Intellectual Capital Disclosure. This study used a sample of conventional banks registered with the Financial Services Authority with a sample of 41 conventional banks during the 2017-2021 period. This study uses panel data regression model analysis. The analysis techniques used in this study were descriptive statistical tests, preliminary tests (Breusch-Pagan, likelihood tests, hausman tests), diagnostic tests (heteroscedasticity tests and autocorrelation tests), and hypothesis testing. Based on the results of the three preliminary tests in determining the panel data regression model, this study will use the random effect model to examine the relationship between variables in the regression model 1, and the fixed effect model in the regression model 2. This study reveals that the audit committee competency variable has a positive effect on Intellectual Capital Disclosure. The ownership concentration variable has no effect on Intellectual Capital Disclosure. Institutional ownership variable has no effect on Intellectual Capital Disclosure. Meanwhile, this study cannot prove the role of the ownership concentration variable in strengthening or weakening the competence of the audit committee on Intellectual Capital Disclosure. Meanwhile, the institutional ownership variable weakens the relationship between audit committee competence and Intellectual Capital Disclosure.